The effect on river discharge estimation by considering an interaction between land surface process and river routing process - Yorozu, K.; Tachikawa, Y. (Proceedings of the International Association of Hydrological Sciences, 2015)
There is much research assessing the impact of climate change on the hydrologic cycle. However, it has often focused on a specific hydrologic process, without considering the interaction among hydrologic processes. In this study, a distributed hydrologic model considering the interaction between flow routing and land surface processes was developed, and its effect on river discharge estimation was investigated. The model enables consideration of flow routing, irrigation withdrawal from rivers at paddy fields, crop growth depending on water and energy status, and evapotranspiration based on meteorological, soil water and vegetation status. To examine the effects of hydrologic process interaction on river discharge estimation, a developed model was applied to the Chao Phraya river basin using near surface meteorological data collected by the Japanese Meteorological Research Institute's Atmospheric General Circulation Model (MRI-AGCM3.2S) with TL959 spatial resolution as forcing data. Also, a flow routing model, which was part of the developed model, was applied independently, using surface and subsurface runoff data from the same GCM. In the results, the developed model tended to estimate a smaller river discharge than was estimated by the river routing model, because of the irrigation effect. In contrast, the annual maximum daily discharge calculated by the developed model was 24% greater than that by the flow routing model. It is assumed that surface runoff in the developed model was greater than that in the flow routing model because the soil water content was maintained at a high level through irrigation withdrawal. As for drought discharge, which is defined as the 355th largest daily discharge, the developed model gave a discharge 2.7-fold greater than the flow routing model. It seems that subsurface runoff in the developed model was greater than that in the flow routing model. The results of this study suggest that considering hydrologic interaction in a numerical model could affect both flood and drought estimation.